MAKNA SIMBOLIK BARU PADA MASJID AGUNG JAWA TENGAH - Kasim, Muhammad Aqil (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
This study aims to find out the new symbolic meaning that lies in the Masjid Agung Jawa Tengah (MAJT) and the commodification process that occurs. This study uses a qualitative method and interpretivism approach. The source of the data resulted from interviews conducted with the administrators, merchants, and visitors in the Masjid Agung Jawa Tengah and observations of archives, photos, and electronic media about Masjid Agung Jawa Tengah. The result of this study shows that the visitors come to Masjid Agung Jawa Tengah for tourism and to fulfill their curiosity desire about the magnificent architecture of Masjid Agung Jawa Tengah. Later, the visitors feel excited and satisfied after they visit Masjid Agung Jawa Tengah. Furthermore, Masjid Agung Jawa Tengah becomes the medium to deliver spiritual and material value to the visitors. Today, many people are looking for economic benefits from Masjid Agung Jawa Tengah. The administrator makes Masjid Agung Jawa Tengah as a place to earn a living. It is the same condition with the merchant and travel startup which looking for economic benefits from the imagery of the Masjid Agung Jawa Tengah